2011
DOI: 10.1080/15228835.2011.639931
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Nurse Perceptions of a Newly Implemented Electronic Medical Record System

Abstract: Nurses are the frontline of healthcare; however, there has been little theoretically-driven research on their acceptance of information technology use in care delivery. This research utilized the unified theory of acceptance and use of technology (UTAUT) model to understand how hospital nurses perceived the implementation of a new electronic medical record (EMR) system. This study used mix methods. The survey responses indicated that social influence and performance expectancy were significant factors in syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 26 publications
(30 reference statements)
8
38
3
Order By: Relevance
“…The findings of the present study showed that of the four influencing factors, performance expectancy was by far the strongest predicting factor playing a major role in the nurses' intention to use information systems. Our results are consistent with a number of prior studies which showed performance expectancy to be more effective in comparison to effort expectancy and social influence (Hamidfar, Limayem & Zegordi 2008;Wu et al 2007;Holtz & Krein 2011;Ifinedo 2012;AlAwadhi 2008;Zhou 2008;Wang & Shih 2009;Chang et al 2007).…”
Section: Discussionsupporting
confidence: 95%
“…The findings of the present study showed that of the four influencing factors, performance expectancy was by far the strongest predicting factor playing a major role in the nurses' intention to use information systems. Our results are consistent with a number of prior studies which showed performance expectancy to be more effective in comparison to effort expectancy and social influence (Hamidfar, Limayem & Zegordi 2008;Wu et al 2007;Holtz & Krein 2011;Ifinedo 2012;AlAwadhi 2008;Zhou 2008;Wang & Shih 2009;Chang et al 2007).…”
Section: Discussionsupporting
confidence: 95%
“…Although, the result of Jason et al's study (19) is consistent with the results of our study, the result of this part of the study is not consistent with those of the Wills et al (15) and Holtz and Krein's studies (27). Although, most of the previous studies signify the relationship between social influences and use intention of technology, this study shows that there is no significant relationship between these two factors.…”
Section: Discussioncontrasting
confidence: 54%
“…Other results of this study showed that there is a significant relationship between Facilitating Condition and Be- (27).…”
Section: Discussionmentioning
confidence: 59%
“…C Co on nt te en nt t v va al li id di it ty y: : In order to generate items for The Usability Scale of the Electronic Record System in terms of Nursing Functions, a detailed literature review was carried out and similar studies were examined. 5,8,12,13,[17][18][19][20][21][22][23] In addition, for generating content validity, a composition on experiences (emotions, thoughts, and behaviors) regarding the relevant topic were requested from the 56 respondents, which corresponded to nurses from every unit. The attitude components reported in the written compositions were systematically examined and were used in combination with information obtained from the literature in order to generate attitude statements.…”
Section: Resultsmentioning
confidence: 99%